2017
DOI: 10.3389/fncel.2017.00372
|View full text |Cite
|
Sign up to set email alerts
|

Cdk5 Is Essential for Amphetamine to Increase Dendritic Spine Density in Hippocampal Pyramidal Neurons

Abstract: Psychostimulant drugs of abuse increase dendritic spine density in reward centers of the brain. However, little is known about their effects in the hippocampus, where activity-dependent changes in the density of dendritic spine are associated with learning and memory. Recent reports suggest that Cdk5 plays an important role in drug addiction, but its role in psychostimulant’s effects on dendritic spines in hippocampus remain unknown. We used in vivo and in vitro approaches to demonstrate that amphetamine incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 128 publications
(154 reference statements)
1
12
0
Order By: Relevance
“…To determine how siRNA loss of VAPB or PTPIP51 affects dendritic spine numbers, we transfected neurons with EGFP to reveal neuronal morphology and identify dendrites; such approaches have been used in many other studies e.g. [8, 11, 49]. We then quantified spine numbers in the same dendritic regions of the different treated neurons (20 μm segments after the first branchpoint).…”
Section: Resultsmentioning
confidence: 99%
“…To determine how siRNA loss of VAPB or PTPIP51 affects dendritic spine numbers, we transfected neurons with EGFP to reveal neuronal morphology and identify dendrites; such approaches have been used in many other studies e.g. [8, 11, 49]. We then quantified spine numbers in the same dendritic regions of the different treated neurons (20 μm segments after the first branchpoint).…”
Section: Resultsmentioning
confidence: 99%
“…CDK5 is a key second messenger participating in METH-induced behavioral sensitization [ 130 , 242 , 243 ]. Both administration of amphetamines and stimulation of D1R induce a significant increase of CDK5 gene expression and protein levels, which, at molecular level, associates with increased dendritic spine density and hyper-phosphorylation of the cytoskeletal tau protein [ 244 , 245 , 246 ]. In detail, the activation of CDK5 by D1R occurs via proteolysis of p35, the binding partner of CDK5.…”
Section: Mtor Modulation Of Dopamine Transmission In Methamphetamimentioning
confidence: 99%
“…Mushroom-type spines represent a more mature population than other types of spines, and their large head/neck ratio is thought to contribute to their function as stable excitatory synapses [ 63 ]. Of note, repetitive amphetamine or methamphetamine treatment induces behavioral sensitization in mice [ 66 , 67 ], which is accompanied by an increase in mushroom-type spine density in MSNs [ 68 , 69 ]. In the present study, we found an increase in mushroom-type spine density in the striatal and accumbal neurons of Arhgap10 S490P/NHEJ mice that have a higher sensitivity to methamphetamine.…”
Section: Discussionmentioning
confidence: 99%